A critical examination of the concept of welfare dependency : its assumptions, underlying values and manifistation in social policy, internationally and in South Africa - Di Lollo, Adrian (Department of Social Development, 2015)
Concern over "welfare dependency" has featured prominently in the public discoursearound social assistance programmes in numerous countries for many years. The notionthat social assistance payments tend to sap the recipient's initiative, independence andpropensity for securing paid employment is widespread and is often assumed to be anobjective fact (rather than a concept) by public officials, social commentators and themedia. Consequently, charges of "welfare dependency" have often been used as the basisfor cutting social assistance expenditure, restricting eligibility or preventing newinitiatives. In South Africa, for example, the concept has been used in opposition todeveloping a universal Basic Income Grant (BIG).With the aid of case studies focusing on recent social welfare deVelopments in SouthAfrica, Australia and Brazil, this study attempts to critically analyse the term "welfaredependency" to determine which social values and assumptions inform the concept. Inaddition, the study aims to determine how "welfare dependency" manifests incontemporary social welfare policy and, most importantly, determine if the utilisation ofthe concept is related to other socio-economic agendas.